Mediation of the proinflammatory cytokine response in rheumatoid arthritis and spondylarthritis by interactions between fibroblast-like synoviocytes and natural killer cells. - Chan, A; Filer, A; Parsonage, G; Kollnberger, S; Gundle, R; Buckley, C; Bowness, P (2008)
OBJECTIVE: Fibroblast-like synoviocytes (FLS) are potentially directly involved in the propagation of inflammation. We have previously shown evidence of an expanded activated population of natural killer (NK) cells in spondylarthritis (SpA) patients. In the present study, we sought to determine whether the interaction between NK cells and FLS from SpA patients results in a proinflammatory response. METHODS: Autologous NK cells and FLS were obtained from 6 patients with SpA, 4 patients with rheumatoid arthritis (RA), and 8 patients with osteoarthritis (OA). Physical interactions between NK cells and FLS were studied by time-lapse phase-contrast microscopy. Fluorescence-activated cell sorting was used to study the activation, proliferation, and survival of NK cells in contact with FLS. Cytokine and stromal factor production were measured by a multiple cytokine bead assay. RESULTS: NK cells both adhered to and migrated beneath the FLS monolayer (pseudoemperipolesis). FLS from SpA and RA patients supported increased pseudoemperipolesis, activation, cytokine production, and survival of NK cells. The production of proinflammatory cytokines, including interleukin-6 (IL-6), IL-8, IL-1beta, and IL-15, was increased in cocultures of NK cells and FLS, particularly in those from RA and SpA patients. Production of interferon-gamma, RANTES, and matrix metalloproteinase 3 (MMP-3) by NK cell and FLS coculture was greatest in SpA patients. Surface expression of IL-15 on FLS was significantly increased in SpA and RA patients, but not OA patients. Blockade with an IL-15 monoclonal antibody resulted in increased apoptosis of NK cells. CONCLUSION: FLS promote the migration, activation, and survival of NK cells. The interaction of NK cells with FLS results in increased IL-15 expression by FLS and the production of proinflammatory chemokines, cytokines, and MMPs, which may contribute to joint inflammation. This response was much more marked in SpA and RA patients as compared with OA patients.